Artificial intelligence (AI) acceptance in primary care during the coronavirus pandemic: What is the role of patients' gender, age and health awareness? A two-phase pilot study - Chalutz Ben-Gal, Hila (Frontiers in Public Health, 2023)
Background. Artificial intelligence (AI) is steadily entering and transforming the health care and Primary Care (PC) domains. AI-based applications assist physicians in disease detection, medical advice, triage, clinical decision-making, diagnostics and digital public health. Recent literature has explored physicians’ perspectives on the potential impact of digital public health on key tasks in PC. However, limited attention has been given to patients’ perspectives of AI acceptance in PC, specifically during the coronavirus pandemic. Addressing this research gap, we administered a pilot study to investigate criteria for patients’ readiness to use AI-based PC applications by analyzing key factors affecting the adoption of digital public health technology. Methods. The pilot study utilized a two-phase mixed methods approach. First, we conducted a qualitative study with 18 semistructured interviews. Second, based on the Technology Readiness and Acceptance Model (TRAM), we conducted an online survey (n=447). Results. The results indicate that respondents who scored high on innovativeness had a higher level of readiness to use AI-based technology in PC during the coronavirus pandemic. Surprisingly, patients’ health awareness and sociodemographic factors, such as age, gender and education, were not significant predictors of AI-based technology acceptance in PC. Conclusions. This paper makes two major contributions. First, we highlight key social and behavioral determinants of acceptance of AI-enabled health care and PC applications. Second, we propose that to increase the usability of digital public health tools and accelerate patients’ AI adoption, in complex digital public health care ecosystems, we call for implementing adaptive, population-specific promotions of AI technologies and applications.